Foreign-currency exposures and the financial channel of exchange rates: Eroding monetary policy autonomy in the Asia and Pacific region? - Georgios Georgiadis; Feng Zhu (Asian Development Bank Institute (ADBI), 2020)
Foreign-currency exposures on an economy's external balance sheet may jeopardize financial stability when the exchange rate depreciates. In fact, theory suggests that in such an environment it may be optimal for monetary policy in a floating regime to reduce exchange rate variation in order to dampen financial cycles by mimicking foreign monetary policy rather than focusing exclusively on stabilizing macroeconomic fundamentals. We explore whether there is evidence in the data for economies facing such a trade-off between financial stability and macroeconomic stabilization that gives rise to fear of floating. In a panel data set for the time period from 2002 to 2012 and 10 small open economies with floating regimes in the Asia and Pacific region we document evidence that is consistent with fear of floating, i.e., that local mimics base-country monetary policy even after controlling for macroeconomic fundamentals. Importantly, we find that this fear of floating is particularly pronounced in the presence of foreign-currency exposures. Specifically, fear of floating is stronger when the foreign-currency exposures arise through debt rather than nondebt instruments, which is consistent with existing evidence documenting that these instruments are more fickle and sensitive to swings in investor sentiment. Moreover, the evidence for fear of floating is stronger when base-country monetary policy is tightened, suggesting that monetary policy tends to act to address immediate threats to financial stability in the face of depreciation pressures rather than to preemptively mitigate the buildup of foreign-currency exposures when the currency is appreciating.
Keywords: F42; E52; C50; 330; foreign-currency exposures; monetary policy autonomy; spillovers